2010
DOI: 10.1111/j.1439-0264.2010.01044.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of Ghrelin in the Stomach of Sprague‐Dawley Rat

Abstract: To investigate the distribution of ghrelin in different regions of stomach in Sprague-Dawley rat, and attempt to compare with those of humans and other mammalian species in this study, the stomach of rats was divided into five sections, cardia, fundus, greater curvature, lesser curvature and pylorus. Immunohistochemistry and Western blotting were performed to investigate the ghrelin-producing cells. The immunolocalization and protein levels of ghrelin differed significantly in different regions of stomach in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Gastric acid secretion is subjected to an important hormonal regulation. The bulk of ghrelin in the body occurs in the A-like cells of the acid-producing part of the stomach, and plasma ghrelin-like immunoreactivity levels in totally gastrectomized patients were reduced to 35% of those in normal controls (Li et al, 2011), which suggested that ghrelin played the important role in regulating gastric acid secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric acid secretion is subjected to an important hormonal regulation. The bulk of ghrelin in the body occurs in the A-like cells of the acid-producing part of the stomach, and plasma ghrelin-like immunoreactivity levels in totally gastrectomized patients were reduced to 35% of those in normal controls (Li et al, 2011), which suggested that ghrelin played the important role in regulating gastric acid secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin increases food intake and decreases energy expenditure, leading to a positive energy balance [15]. There was a potential use of ghrelin for gastrointestinal diseases [12] and temperature regulation [16]. The pharmacologic actions of ALZ involved energy charges [9, 10] and ATPase activity [11].…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemical localization of ghrelin was detected according to the method described by Li et al [12] with some modification. After the tissue sections (6  μ m) were treated with 3% normal goat serum for 1 h at 25°C, then rabbit polyclonal antibody (Santa Cruz) against rat ghrelin was applied to the gastric sections (1 : 200) and incubated overnight.…”
Section: Methodsmentioning
confidence: 99%
“…The tissues were thawed, cut into small pieces and kept at 4 °C in a glass container containing 4 volumes of cold HB. The tissues were homogenised five times with a Polytron PT1200 (Kinematica AG, Switzerland) and then centrifuged at 12 000 g for 30 min at 4 °C . The supernatant was collected with care to avoid fat contamination, aliquoted and stored at −70 °C until used.…”
Section: Methodsmentioning
confidence: 99%